Present situation and Prospect of scientific research on local products - Jing, Zhang; Na, Lei (International Journal of Agriculture and Food Sciences Research, 2025)
As a local characteristic resource, local products have important economic, cultural and ecological values. This paper discusses the current situation and future development direction of the scientific research on indigenous products from three dimensions: planting suitability and soil research, technological innovation and product development, sustainable development and ecological protection. By analyzing the research progress of soil and climate factors, nutrient management, geographical indications and standardization, variety improvement, processing technology, digital application and other aspects, this paper puts forward strategic suggestions to promote the high-quality development of local products industry, aiming to provide reference for the research and practice in related fields.